Aging-related biomarker discovery in the era of immune checkpoint inhibitors for cancer patients - Al-Danakh, Abdullah; Safi, Mohammed; Jian, Yuli; Yang, Linlin; Zhu, Xinqing; Chen, Qiwei; Yang, Kangkang; Wang, Shujing; Zhang, Jianjun; Yang, Deyong (Frontiers in Immunology, 2024)
Older patients, particularly those over 75 years of age, often experience poorer clinical outcomes compared to younger patients. This can be attributed to age-related comorbidities, weakened immune function, and reduced tolerance to treatment-related adverse effects. In the immune checkpoint inhibitors (ICI) era, age has emerged as an influential factor impacting the discovery of predictive biomarkers for ICI treatment. These age-linked changes in the immune system can influence the composition and functionality of tumor-infiltrating immune cells (TIICs) that play a crucial role in the cancer response. Older patients may have lower levels of TIICs infiltration due to age-related immune senescence particularly T cell function, which can limit the effectivity of cancer immunotherapies. Furthermore, age-related immune dysregulation can lead to an increase in the exhaustion of the immune cells, characterized by the dysregulation of ICI-related biomarkers. Consequently, this exhaustion can dampen the response to ICI targeting these checkpoints. Our review aims to provide a comprehensive understanding of the mechanisms that contribute to the impact of age on ICI-related biomarkers. By gaining insights into these mechanisms, we aim to facilitate the development of personalized treatment approaches tailored for elderly individuals diagnosed with cancer.